METHODOLOGY FOR ASSESSING THE EFFICIENCY OF SPECIAL ECONOMIC ZONES IN THE CONTEXT OF THE DIGITAL ECONOMY (Multidisciplinary Journal of Science and Technology, 2025)
The article analyzes the methodological foundations for assessing the efficiency of special economic zones (SEZs) under the conditions of the digital economy. The study examines the impact of digital technologies and fiscal incentive mechanisms on industrial production and employment. A system of indicators is proposed to measure efficiency in the digital economic environment, including the tax incentive efficiency coefficient and the digital investment index. Based on the research findings, the paper substantiates the potential for improving the performance of SEZs through the implementation of digital management systems, the use of automated tax platforms, and the optimization of information flows.